Negative electrode material and preparation method and application thereof

By performing thermal treatment and multi -step carbonization treatment under negative pressure, optimize the structure of the negative electrode material of lithium -ion battery, solve the problems of insufficient negative materials in the existing technologies and the preparation methods, and achieve high -performance negative electrode materials Preparation.

CN119361636APending Publication Date: 2025-01-24LIYANG ZICHEN NEW MATERIALS TECH CO LTD +1

Patent Information

Application Number
CN202411470673.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have shortcomings in terms of high energy density, rate performance and long cycle life, and the preparation method has the use of a large number of modifiers, large equipment investment, complex processes, dangerous, and harmful to the environment and operators.

Method used

By performing thermal treatment under negative pressure, the mixed system of graphite skeleton and organic carbon source is performed for low -temperature carbonization, oxidation and ablation, and high -temperature carbonization treatment to control the thickness of the non -fixed carbon coating layer and the ID/IG ratio of the Raman spectrum. Optimize the structure and performance of negative materials.

Benefits of technology

It achieves high compaction density, high capacity, low expansion rate, good rate performance and high temperature cycle performance of the negative electrode material, and the preparation method is simple, easy, environmentally friendly and safe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361636A_ABST
    Figure CN119361636A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative electrode material and a preparation method and application thereof. The negative electrode material comprises a composite particle, the composite particle comprises an inner core and an amorphous carbon coating layer located on the surface of the inner core, and the inner core comprises a graphite skeleton and amorphous carbon filled in the graphite skeleton; the thickness of the amorphous carbon coating layer is 10 to 50 nm; raman spectrum surface scanning is carried out on the negative electrode material, the number of Raman spectrum surface scanning points is 400, the average value of ID / IG of the Raman spectrum of the negative electrode material is 0.10-0.20, and the number of the scanning points with the ID / IG single point value smaller than 0.2 accounts for larger than 60%. The graphite-like microchip layers on the surface of the negative electrode material are stacked more regularly, the thickness of the amorphous carbon coating layer is appropriate, and the negative electrode material has high compaction density, high capacity, low expansion rate, good rate capability and good high-temperature cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention application is a divisional application with application number 202410790233X, application date June 19, 2024, and invention name “Negative electrode material, preparation method and application thereof”. Technical Field

[0002] The present invention relates to the field of battery technology, and in particular to a negative electrode material and a preparation method and application thereof. Background Art

[0003] As a new type of rechargeable battery, lithium-ion battery has the advantages of high operating voltage, large specific capacity, gentle discharge potential curve, low self-discharge, long cycle life, good low temperature performance, environmental protection, no pollution, no memory effect, etc. It is widely used in 3C products, power devices and energy storage equipment. In recent years, with the increasing requirements of electronic products, automotive cutting and energy storage equipment for miniaturization, light weight, multi-function and long-term driving, the requirements for lithium-ion batteries with high energy density, high rate performance and long cycle life are constantly increasing.

[0004] Prior art literature:

[0005] Document 1: Chinese patent CN114843508A;

[0006] Document 2: Chinese patent CN114873591A;

[0007] Document 3: Chinese patent CN116730333A.

[0008] After in-depth research, the applicant of the present invention found that:

[0009] Document 1 discloses a modified natural graphite material and its preparation method, negative electrode plate and lithium-ion battery. Due to the large amount of modifier used, the carbonized product has high mechanical strength, low compaction density and poor high-temperature cycle performance.

[0010] Document 2 discloses a low-temperature, long-life natural graphite negative electrode material, its preparation method and use. This method requires large equipment investment, complex and dangerous procedures, uses a large amount of low-temperature asphalt, and has a thick amorphous carbon coating on the surface of the natural graphite after carbonization, resulting in high mechanical strength of the carbonized product, low material compaction density, and poor high-temperature performance; the large amount of solvent used is harmful to the environment and operators.

[0011] Document 3 discloses a method for preparing a modified natural graphite negative electrode material, which uses a large amount of toxic and harmful organic cleaning agents, causing harm to the environment and operators. Summary of the invention

[0012] One object of the present invention is to provide a negative electrode material, the graphite-like micro-chip layer on its surface is more regularly stacked, the thickness of the amorphous carbon coating layer is appropriate, it has high compaction density, high capacity, low expansion rate, good rate performance, and good high-temperature cycle performance.

[0013] Another object of the present invention is to provide a method for preparing the negative electrode material. The method is simple and easy to implement. Through the coordination of various steps, the thickness of the amorphous carbon coating layer can be controlled within an appropriate range, the surface defect content can be reduced, the capacity and compaction of the negative electrode material can be improved, the expansion rate can be reduced, and the high-temperature cycle performance can be good.

[0014] Another object of the present invention is to provide a negative electrode sheet.

[0015] Another object of the present invention is to provide a battery.

[0016] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0017] A negative electrode material comprises composite particles, wherein the composite particles comprise a core and an amorphous carbon coating layer located on the surface of the core, the core comprises a graphite skeleton and amorphous carbon filled in the graphite skeleton; the thickness of the amorphous carbon coating layer is 10 to 50 nm; a Raman spectrum surface scan is performed on the negative electrode material, the Raman spectrum surface scanning points are 400, the average ID / IG value of the Raman spectrum of the negative electrode material is 0.10 to 0.20, wherein the number of scanning points with single point values ​​of ID / IG less than 0.2 accounts for more than 60%.

[0018] In some embodiments, the amorphous carbon coating layer has a thickness of 10 to 30 nm.

[0019] In some embodiments, the average ID / IG value of the Raman spectrum of the negative electrode material is 0.10-0.14, wherein the number of scanning points with a single point value of ID / IG less than 0.2 accounts for 65%-91%.

[0020] In some embodiments, the particle size Dv50 of the graphite skeleton is 5 to 25 μm.

[0021] In some embodiments, the graphite skeleton comprises natural graphite.

[0022] In some embodiments, the pore volume of the graphite skeleton is 0.02 to 0.05 cm 3 / g 。

[0023] In some embodiments, the compaction density of the negative electrode material under 2 tons of pressure is greater than 1.65 g / cm 3 .

[0024] In some embodiments, the interlayer spacing d002 of the X-ray diffraction pattern of the negative electrode material is 0.335775-0.335934 nm.

[0025] In some embodiments, the true density of the negative electrode material is greater than 2.190 g / cm 3 .

[0026] In some embodiments, the pore volume of the negative electrode material is less than 0.005 cm 3 / g;

[0027] In some embodiments, the gram capacity of the negative electrode material is greater than 360 mAh / g.

[0028] In some embodiments, the first coulombic efficiency of the negative electrode material is greater than 94%.

[0029] A method for preparing a negative electrode material comprises the following steps:

[0030] The mixed system of graphite skeleton and organic carbon source is subjected to heat treatment under negative pressure to obtain a first material; the first material is subjected to low-temperature carbonization treatment, oxidation ablation treatment and high-temperature carbonization treatment in sequence.

[0031] In some embodiments, the graphite skeleton comprises natural graphite.

[0032] In some embodiments, the particle size D50 of the graphite skeleton is 5 to 25 μm, and the carbon content of the graphite skeleton is greater than 99.9%.

[0033] In some embodiments, the pore volume of the graphite skeleton is 0.02 to 0.05 cm 3 / g;

[0034] In some embodiments, the organic carbon source includes at least one of petroleum pitch, coal tar pitch and thermoplastic resin.

[0035] In some embodiments, the organic carbon source has a coking value greater than 70% when heated at 550° C. in a protective atmosphere for 2 hours.

[0036] In some embodiments, the mass ratio of the graphite skeleton to the organic carbon source is 75:25 to 90:10.

[0037] In some embodiments, the vacuum degree during the heat treatment process is an absolute pressure less than 0.05 MPa.

[0038] In some embodiments, the vacuum degree of the environment in which the mixed system is located before the heat treatment is an absolute pressure less than 0.03 MPa.

[0039] In some embodiments, the heat treatment temperature is 300-500° C., and the heat treatment time is 1-5 hours.

[0040] In some implementations, during the heat treatment, the mixed system is stirred at a speed of 100 to 300 r / min.

[0041] In some embodiments, the method further comprises: cooling the heat-treated material to room temperature.

[0042] In some embodiments, the second material obtained by the low-temperature carbonization treatment has a volatile matter content of less than 2% and a graphitization degree of 89% to 92%.

[0043] In some embodiments, the temperature of the low-temperature carbonization treatment is 500-800° C., and the time of the low-temperature carbonization treatment is 2-8 hours.

[0044] In some embodiments, the low-temperature carbonization treatment is performed under protective gas conditions.

[0045] In some embodiments, the third material obtained by the oxidation ablation treatment comprises a graphite core and an amorphous carbon layer; the average thickness of the amorphous carbon layer is 100 to 300 nm; the average value of ID / IG of the Raman spectrum of the third material is 0.19 to 0.50; the powder compaction density of the third material under a pressure of 2 tons is greater than 1.55 g / cm 3 ; The interlayer spacing d002 of the X-ray diffraction pattern of the third material is 0.335932~0.336270nm.

[0046] In some embodiments, the temperature of the oxidation ablation treatment is 600-900° C., and the time of the oxidation ablation treatment is 3-10 hours.

[0047] In some embodiments, the atmosphere of the oxidation ablation treatment is an oxygen-containing atmosphere with a flow rate of 1 to 5 m 3 / h.

[0048] In some embodiments, the temperature of the high temperature carbonization treatment is 1500-1800° C., and the time of the high temperature carbonization treatment is 6-12 hours.

[0049] In some embodiments, the high temperature carbonization treatment is performed under protective gas conditions.

[0050] A negative electrode sheet comprises the negative electrode material or the negative electrode material prepared by the negative electrode material preparation method.

[0051] A battery comprises the negative electrode sheet.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] (1) The negative electrode material of the present invention has an amorphous carbon coating layer of suitable thickness, a small ID / IG of the Raman spectrum of the negative electrode material, and a high content of points with a single point value of ID / IG less than 0.2, indicating that the defect content of the graphite-like microcrystals on the surface of the negative electrode material is low, and the graphite-like microcrystal layer is more regularly stacked. The negative electrode material has a high compaction density, high capacity, low expansion rate, good rate performance, and good high-temperature cycle performance.

[0054] (2) The present invention fills a large amount of organic carbon source into the interior of graphite particles and coats the surface of graphite particles by means of high temperature and negative pressure, and uses low temperature carbonization treatment to solidify and shape the organic carbon source to convert it into amorphous carbon, discharge volatiles, and make the amorphous carbon have good reaction activity and the size of graphite-like crystallites is relatively uniform; further, an oxidative ablation method is used to control the thickness of the amorphous carbon coating layer on the surface of the particles within an appropriate range, thereby improving the compaction density of the material, the volume energy density of the battery cell and the mass energy density, reducing the proportion of active sites in the residual amorphous carbon layer on the surface, and reducing the side reaction of amorphous carbon with the electrolyte; further, a high temperature carbonization treatment is used to recrystallize and discharge the remaining volatiles of the amorphous carbon after the oxidative ablation treatment, thereby reducing the defect sites of the amorphous carbon and reducing the specific surface area; the coordination of each step can obtain a negative electrode material with high capacity, high compaction, low expansion rate and good rate performance, which can greatly improve the high temperature performance of the material.

[0055] (3) The battery obtained by the negative electrode material of the present invention has high capacity, high initial efficiency, high rate performance, and excellent high temperature cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0057] Figure 1 This is an argon ion polishing scanning electron microscope image of the negative electrode material in Example 2 of the present invention, with a magnification of 3000 times;

[0058] Figure 2 This is an argon ion polishing scanning electron microscope image of the negative electrode material in Example 2 of the present invention, with a magnification of 50,000 times;

[0059] Figure 3 This is the ID / IG distribution diagram of the negative electrode material in Example 2 of the present invention;

[0060] Figure 4 This is a scanning electron microscope image of the negative electrode material in comparative example 1 of the present invention after argon ion polishing;

[0061] Figure 5 This is the ID / IG distribution diagram of the negative electrode material in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0062] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0063] According to a negative electrode material of the present invention, the composite particles include a core and an amorphous carbon coating layer located on the surface of the core, the core includes a graphite skeleton and amorphous carbon filled in the graphite skeleton; the thickness of the amorphous carbon coating layer is 10 to 50 nm; the negative electrode material is subjected to a Raman spectrum surface scan, the Raman spectrum surface scanning points are 400, and the average ID / IG (peak intensity ratio) of the Raman spectrum of the negative electrode material is 0.10 to 0.20, wherein the number of scanning points with a single point value of ID / IG less than 0.2 accounts for more than 60%.

[0064] The negative electrode material of the present invention has an amorphous carbon coating layer of suitable thickness, a small ID / IG of the Raman spectrum of the negative electrode material, and a high content of points with a single point value of ID / IG less than 0.2, indicating that the defect site content of the graphite-like microcrystals on the surface of the negative electrode material is low, the graphite-like microcrystal layer is more regularly stacked, and the negative electrode material has a high compaction density, a high capacity, a low expansion rate, a good rate performance, and a good high-temperature cycle performance.

[0065] In some embodiments, the thickness of the amorphous carbon coating layer is 10 to 50 nm, for example, it can be but not limited to 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 50 nm, etc., or a range of any two of them. The amorphous carbon coating layer of the present invention has the above-mentioned suitable thickness, which is beneficial to increase the gram capacity of the material and increase the compaction density of the material. Preferably, the thickness of the amorphous carbon coating layer is 10 to 30 nm.

[0066] In some embodiments, the average value of ID / IG of the Raman spectrum of the negative electrode material is 0.10-0.20, for example, it can be but not limited to 0.10, 0.12, 0.15, 0.18 or 0.20, or a range value composed of any two. The Raman spectrometer scans 400 points, wherein the number of scanning points with a single point value of ID / IG less than 0.2 accounts for more than 60%, for example, it can be but not limited to 61%, 65%, 68%, 70%, 72%, 75%, 80%, 85%, 90%, 91%, 95%, 96% or 98%, or a range value composed of any two. The average value of ID / IG of the Raman spectrum of the negative electrode material of the present invention is low, the lower the defect content of the surface negative electrode material, the more regular the stacking of the graphite-like microcrystalline layer remaining on the surface of the negative electrode material, and thus the compatibility of the graphite-like microcrystals on the surface of the coating layer with the electrolyte is better, and the high temperature cycle performance of the negative electrode material is excellent.

[0067] In some embodiments, the average ID / IG value of the Raman spectrum of the negative electrode material is 0.10-0.14, wherein the number of scanning points with a single point value of ID / IG less than 0.2 accounts for 65%-91%.

[0068] The average ID / IG of the Raman spectrum of pure graphitized products of graphite materials (such as artificial graphite and natural graphite) is usually between 0.03 and 0.05, and the number of scanning points with single-point values ​​of ID / IG less than 0.1 accounts for more than 99%. The graphite crystals have good crystal purity, resulting in relatively poor rate performance of pure graphitized products, which can be improved by carbon coating. When the ID / IG of the amorphous carbon in the surface coating layer gradually increases, the crystallinity of the graphite-like crystals in the amorphous carbon begins to deteriorate and the crystal defects increase, the rate performance of the material improves, and the high-temperature cycle performance deteriorates.

[0069] Without being bound by theory, the applicant of the present invention has found that ID / IG=0.2 is the critical value for the degradation of the high-temperature cycle performance of the amorphous carbon coating layer. When ID / IG exceeds 0.2, the rate performance is excellent and the high-temperature cycle is poor. When ID / IG is 0.1-0.2, both the rate performance and the high-temperature cycle performance can be taken into account. When ID / IG is less than 0.1, the high-temperature cycle performance is excellent and the rate performance is poor. When the number of scanning points with a single point value of ID / IG less than 0.2 accounts for 65% to 91%, both better rate performance and high-temperature cycle performance can be taken into account.

[0070] In some embodiments, the particle size Dv50 of the graphite skeleton is 5 to 25 μm, for example, it can be but not limited to 5 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm or 25 μm, or a range of any two thereof.

[0071] In some embodiments, the particle size Dv50 of the graphite skeleton is 10 to 20 μm.

[0072] In some embodiments, the graphite skeleton comprises natural graphite. In other embodiments, the graphite skeleton may also be artificial graphite. In the present invention, the graphite skeleton preferably comprises natural graphite. Natural graphite has many surface defects and well-developed pores, which have an adverse effect on its large-scale application. The present invention can be used as a high-performance negative electrode material after modifying natural graphite.

[0073] In some embodiments, the pore volume of the graphite skeleton is 0.02 to 0.05 cm 3 / g, for example, it can be but not limited to 0.02cm 3 / g, 0.025cm 3 / g, 0.03cm 3 / g, 0.035cm 3 / g, 0.04cm 3 / g, 0.045cm 3 / g, 0.048cm 3 / g or 0.05cm 3 / g, etc., or a range value composed of any two. The graphite skeleton of the present invention has a suitable pore volume, which can enable the final negative electrode material to obtain excellent comprehensive performance. If the pore volume is too high, more amorphous carbon needs to be filled, resulting in low compaction density and low gram capacity of the final product; if the pore volume is too small or there are basically no pores (that is, basically solid spheres or sheets), amorphous carbon cannot be filled into the particles, resulting in slow diffusion of lithium ions inside the particles during lithium insertion and extraction, which is not conducive to the improvement of rate performance.

[0074] In some embodiments, the compaction density of the negative electrode material under 2 tons of pressure is greater than 1.65 g / cm 3 , for example, but not limited to 1.66 g / cm 3 , 1.67g / cm 3 、1.68g / cm 3 , 1.69g / cm 3 , 1.70g / cm 3 , 1.71g / cm 3 Preferably, the compaction density of the negative electrode material under a pressure of 2 tons is greater than 1.65 g / cm 3 , and less than or equal to 1.75g / cm 3 The negative electrode material of the present invention has a suitable compaction density, which can ensure full contact between particles, not block the ion movement channel, ensure good conductivity of electrons and rapid ion movement during large current discharge, reduce discharge polarization, increase discharge platform voltage, and improve battery rate performance and cycle performance.

[0075] In some embodiments, the interlayer spacing d002 of the X-ray diffraction pattern of the negative electrode material is 0.335775-0.335934 nm, for example, it can be but not limited to 0.335775 nm, 0.335815 nm, 0.335875 nm, 0.335915 nm, etc., or a range of any two of them. The negative electrode material of the present invention has a suitable interlayer spacing d002, and the negative electrode material has a high degree of graphitization.

[0076] In some embodiments, the true density of the negative electrode material is greater than 2.190 g / cm 3 , for example, but not limited to 2.203 g / cm 3 , 2.215g / cm 3 , 2.228g / cm 3 , 2.237g / cm 3 Preferably, the true density of the negative electrode material is 2.210-2.240 g / cm 3 The negative electrode material of the present invention has a suitable true density, thereby ensuring that the battery has excellent energy density and specific capacity.

[0077] In some embodiments, the pore volume of the negative electrode material is less than 0.005 cm 3 / g, for example, it can be but not limited to 0.001cm 3 / g, 0.002cm 3 / g, 0.003cm 3 / g, 0.004cm 3 / g, 0.0045cm 3 / g, etc., or a range value composed of any two. The negative electrode material of the present invention has a smaller pore volume, which can reduce the side reaction between the surface of the negative electrode material and the electrolyte, and is conducive to improving the high temperature cycle performance.

[0078] In some embodiments, the gram capacity of the negative electrode material is greater than 360 mAh / g, for example, it can be but not limited to 365 mAh / g, 368 mAh / g, 370 mAh / g, etc., or a range of any two values. Preferably, the gram capacity of the negative electrode material is: greater than 360 mAh / g and less than or equal to 364 mAh / g. The negative electrode material of the present invention has a high gram capacity and excellent cycle performance.

[0079] In some embodiments, the first coulombic efficiency of the negative electrode material is greater than 94%, for example, it can be but not limited to 94.5%, 95%, 95.5%, 96%, 96.5% or 97%, or a range of any two of them. Preferably, the first coulombic efficiency of the negative electrode material is greater than 94% and less than or equal to 95.2%. The negative electrode material of the present invention has excellent first coulombic efficiency.

[0080] According to another aspect of the present invention, the present invention also relates to a method for preparing a negative electrode material, comprising the following steps:

[0081] The mixed system of the graphite skeleton and the organic carbon source is subjected to heat treatment under negative pressure to obtain a first material. The first material is subjected to low-temperature carbonization treatment, oxidation ablation treatment and high-temperature carbonization treatment in sequence.

[0082] The present invention fills a large amount of organic carbon source into the interior of graphite particles and coats the surface of graphite particles by means of high temperature negative pressure, and then solidifies and shapes the organic carbon source by low temperature carbonization to convert it into amorphous carbon. Without being bound by theory, the applicant of the present invention has found that the material obtained at this time faces the problem of too thick surface coating layer, because the conventional organic carbon source does not have directional selectivity when filling, and they cannot spontaneously gather into the pores inside the particles. In order to ensure the filling effect inside the particles, a large amount of organic carbon source must be added. Even if a certain external force (negative pressure, high pressure or mechanical stirring) is applied, the surface coating layer of the amorphous carbon source is too thick. ), eventually a thick layer of organic carbon source will be coated on the surface of the particles. After carbonization, these amorphous carbons not only fill the interior of the particles in large quantities, but also form a thick coating on the surface of the particles. The surface-coated amorphous carbon has many active sites, which has great advantages in improving the low-temperature performance and rate performance of negative electrode materials. However, too much amorphous carbon coated on the surface will increase the rigidity of the material, resulting in a low compaction density of the material, which is not conducive to improving the volume energy density of the battery cell. In addition, the theoretical gram capacity of amorphous carbon is low, which will also reduce the overall gram capacity of the material, resulting in a low mass energy density of the battery cell. On the other hand, too much amorphous carbon will aggravate the side reaction with the electrolyte in a high temperature environment, causing the high-temperature cycle performance of the material to drop excessively, and in severe cases, it will induce thermal runaway. Faced with this situation, the present invention adopts an oxidative ablation treatment method to first control the thickness of the amorphous carbon coating layer on the surface of the particles within a certain range, which not only improves the compaction density of the material, the volume energy density of the battery cell, and the mass energy density, but also reduces the proportion of active sites in the residual amorphous carbon layer on the surface (in the oxidative ablation process, oxygen molecules first react with carbon microcrystals with good activity and many defects, and then react with carbon microcrystals with slightly weaker activity and regular structure. The whole process appears to be ablation of carbon microcrystals layer by layer on a macro scale), reduces the side reactions between amorphous carbon and the electrolyte, and greatly improves the high temperature performance of the material.

[0083] In some embodiments, the graphite skeleton comprises natural graphite. In other embodiments, the graphite skeleton may also be artificial graphite. In the present invention, the graphite skeleton preferably comprises natural graphite. Natural graphite has many surface defects and well-developed pores, which have an adverse effect on its large-scale application. The present invention can be used as a high-performance negative electrode material after modifying natural graphite.

[0084] In some embodiments, the particle size D50 of the graphite skeleton is 5 to 25 μm, for example, it can be but not limited to 5 μm, 10 μm, 15 μm, 20 μm or 25 μm, or any range of two values. The carbon content of the graphite skeleton is greater than 99.9%. The graphite skeleton of the present invention adopts a suitable particle size to ensure subsequent coating and the electrochemical performance of the negative electrode material.

[0085] In some embodiments, the pore volume of the graphite skeleton is 0.02 to 0.05 cm 3 / g. The graphite skeleton of the present invention has a suitable pore volume, which can enable the final negative electrode material to obtain excellent comprehensive performance. If the pore volume is too high, more amorphous carbon needs to be filled, resulting in low compaction density and low gram capacity of the final product; if the pore volume is too small or there are basically no pores (that is, basically in the form of a solid sphere or sheet), amorphous carbon cannot be filled into the particles, resulting in slow diffusion of lithium ions inside the particles during lithium insertion and extraction, which is not conducive to improving the rate performance.

[0086] In some embodiments, the organic carbon source includes at least one of petroleum asphalt, coal tar pitch and thermoplastic resin, such as a combination of petroleum asphalt and coal tar pitch, a combination of coal tar pitch and thermoplastic resin, etc. In some embodiments, the coking value of the organic carbon source when heated at 550° C. in a protective atmosphere for 2 hours is greater than 70%, such as but not limited to 72%, 75%, 78%, 80%, 82%, 85%, 90%, etc., or a range of any two values.

[0087] In some embodiments, the mass ratio of the graphite skeleton and the organic carbon source is 75:25 to 90:10, for example, it can be but not limited to 75:25, 78:22, 80:20, 85:15, 90:10, etc., or a range value composed of any two. The graphite skeleton and the organic carbon source of the present invention adopt a suitable mass ratio, thereby ensuring that the pores of the graphite skeleton can enter the organic carbon source, and the surface is coated with a suitable thickness of the carbon source, that is, the inner core pores of the final negative electrode material can be filled with a suitable amount of amorphous carbon, and the surface of the core is coated with a suitable amount and thickness of an amorphous carbon coating layer, thereby ensuring that the negative electrode material has a low expansion rate, good rate performance, and excellent high temperature cycle performance.

[0088] In some embodiments, the vacuum degree during the heat treatment process is an absolute pressure of less than 0.05Mpa, for example, it can be but not limited to 0.02Mpa, 0.03Mpa, 0.05Mpa, etc., or a range of values ​​composed of any two. In some embodiments, the vacuum degree of the environment in which the mixed system is located before the heat treatment is an absolute pressure of less than 0.03Mpa, for example, it can be but not limited to 0.005Mpa, 0.01Mpa, 0.02Mpa, etc., or a range of values ​​composed of any two. The vacuum degree of the environment in which the mixed system is located before the heat treatment refers to: putting the mixed system into a reactor, and evacuating the sealed reactor until the vacuum degree is an absolute pressure of less than 0.03Mpa.

[0089] In some embodiments, the temperature of the heat treatment is 300-500°C, for example, it can be but not limited to 300°C, 350°C, 400°C, 450°C, 500°C, etc., or a range of any two. The time of the heat treatment is 1-5h, for example, it can be but not limited to 1h, 2h, 3h, 4h or 5h, etc., or a range of any two. In some embodiments, during the heat treatment, the mixed system is stirred, and the speed of the stirring treatment is 100-300r / min, for example, it can be but not limited to 100r / min, 150r / min, 200r / min, 250r / min or 300r / min, etc., or a range of any two. In some embodiments, it also includes: cooling the heat-treated material to room temperature. The present invention adopts suitable heat treatment temperature, time, and stirring speed to ensure that the organic carbon source can better enter the pore structure of the graphite skeleton and be coated on its surface.

[0090] In some embodiments, the temperature of the low-temperature carbonization treatment is 500-800°C, for example, it can be but not limited to 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc., or a range of any two. The time of the low-temperature carbonization treatment is 2-8h, for example, it can be but not limited to 2h, 2.5h, 3h, 4h, 5h, 6h, 7h or 8h, etc., or a range of any two. The low-temperature carbonization treatment is carried out under protective gas conditions. In some embodiments, the second material obtained by the low-temperature carbonization treatment has a volatile content of less than 2%, for example, it can be but not limited to 0.5%, 1%, 1.5%, 1.8%, etc., or a range of any two. The degree of graphitization is 89%-92%, for example, it can be but not limited to 89%, 90%, 91% or 92%, etc., or a range of any two. The effects of the low-temperature carbonization treatment of the present invention include: 1) exhausting volatiles to prevent deflagration during oxidation and ablation, which is beneficial to production safety; 2) low-temperature carbonization treatment at an appropriate temperature obtains amorphous carbon with good reaction activity and relatively uniform graphite-like crystallite size, which is beneficial to subsequent oxidation and ablation to control the thickness of the amorphous carbon layer.

[0091] In some embodiments, the third material obtained by the oxidation ablation treatment includes a graphite core and an amorphous carbon layer; the average thickness of the amorphous carbon layer is 100-300nm, for example, but not limited to 100nm, 150nm, 180nm, 200nm, 250nm, 300nm, etc., or a range of values ​​consisting of any two. The average value of ID / IG of the Raman spectrum of the third material is 0.19-0.50, for example, but not limited to 0.19, 0.2, 0.22, 0.25, 0.3, 0.4, 0.5, etc., or a range of values ​​consisting of any two. The powder compaction density of the third material under a pressure of 2 tons is greater than 1.55g / cm 3 , for example, but not limited to 1.55 g / cm 3 , 1.28g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 The interlayer spacing d002 of the X-ray diffraction pattern of the third material is 0.335932-0.336270 nm, for example, but not limited to 0.335932 nm, 0.336032 nm, 0.336055 nm, 0.336270 nm, etc., or a range of any two thereof.

[0092] In some embodiments, the temperature of the oxidation ablation treatment is 600-900°C, for example, it can be but not limited to 600°C, 650°C, 700°C, 750°C, 800°C, 900°C, etc., or a range of any two. The time of the oxidation ablation treatment is 3-10h, for example, it can be but not limited to 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc., or a range of any two. The atmosphere of the oxidation ablation treatment is an oxygen-containing atmosphere, such as air, with a flow rate of 1-5m 3 / h, for example, but not limited to 1m 3 / h、2m 3 / h、5m 3 / h, etc., or a range value composed of any two. The present invention adopts appropriate oxidation ablation treatment conditions to control the thickness of the amorphous carbon coating layer on the particle surface within an appropriate range, so as to improve the compaction density of the material, the volume energy density of the battery cell, and the mass energy density, and more effectively reduce the proportion of active sites in the surface residual amorphous carbon layer, reduce the side reaction of amorphous carbon with the electrolyte, and significantly improve the high temperature performance of the negative electrode material.

[0093] In some embodiments, the temperature of the high temperature carbonization treatment is 1500-1800°C, for example, it can be but not limited to 1500°C, 1550°C, 1600°C, 1650°C, 1700°C, 1800°C, etc., or a range of any two values; the time of the high temperature carbonization treatment is 6-12h, for example, it can be but not limited to 6h, 7h, 8h, 9h, 10h, 12h, etc., or a range of any two values. The high temperature carbonization treatment is carried out under protective gas conditions, such as nitrogen and inert gas. The present invention adopts suitable high temperature carbonization treatment conditions to recrystallize and discharge residual volatiles of amorphous carbon after oxidation ablation treatment, reduce defect sites of amorphous carbon, reduce specific surface area, and improve high temperature cycle performance.

[0094] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet, comprising the negative electrode material described above, or the negative electrode material prepared by the method for preparing the negative electrode material described above.

[0095] The negative electrode sheet of the present invention comprises a negative electrode current collector and a negative electrode material layer arranged on at least one side surface of the negative electrode current collector; the negative electrode material layer comprises the above-mentioned negative electrode material.

[0096] According to another aspect of the present invention, the present invention also relates to a battery, comprising the negative electrode sheet.

[0097] The battery of the present invention comprises the above-mentioned negative electrode sheet, positive electrode sheet, separator and electrolyte.

[0098] The battery of the present invention has excellent rate performance, low expansion rate and excellent high temperature cycle performance.

[0099] The following is further explained in conjunction with specific embodiments and comparative examples.

[0100] Example 1

[0101] A method for preparing a negative electrode material comprises the following steps:

[0102] (1) 2.5 kg of coal tar pitch (coking value 75%) and 7.5 kg of natural graphite (D50 = 5 μm, carbon content 99.91%, pore volume 0.05 cm 3 / g) are added into a mixing device and stirred at high speed to mix the materials evenly to obtain a mixed material.

[0103] (2) Place the mixed material into a reactor and evacuate the sealed reactor until the vacuum degree reaches an absolute pressure of 0.02 MPa.

[0104] (3) The reactor with qualified vacuum degree is heated and stirred at a temperature of 300° C., a rotation speed of 300 r / min, and a holding time of 5 h. During the holding period, the vacuum degree is maintained at an absolute pressure of 0.02 MPa. After heating is completed and cooled, the material is released to obtain the first material.

[0105] (4) The first material is subjected to low-temperature carbonization treatment at a temperature of 500° C. for 8 hours in a nitrogen atmosphere. After the heating is completed and the material is cooled to room temperature, a second material is obtained. The second material has a volatile matter content of 1.8% and a graphitization degree of 89.0%.

[0106] (5) The second material is subjected to oxidation ablation treatment at a temperature of 600°C, a time of 10 hours, and an air flow rate of 5 m 3 / h, after heating, cooling to room temperature, the third material was obtained. The average thickness of amorphous carbon in the third material was 200nm, the average ID / IG (peak intensity ratio) of 400 points scanned by Raman spectrometer was 0.50, and the compacted density of the powder under 2 tons was 1.56g / cm 3 , D002 measured by XRD is 0.336270nm.

[0107] (6) The third material is subjected to high-temperature carbonization treatment at a temperature of 1500° C. for 6 hours in a nitrogen atmosphere, and then cooled to room temperature to obtain a natural graphite negative electrode material.

[0108] Example 2

[0109] A method for preparing a negative electrode material comprises the following steps:

[0110] (1) 1.5 kg of petroleum asphalt (coking value 75%) and 8.5 kg of natural graphite (D50 = 15 μm, carbon content 99.95%, pore volume 0.034 cm 3 / g) are added into a mixing device and stirred at high speed to mix the materials evenly to obtain a mixed material.

[0111] (2) The mixed material is placed in a reactor, and the sealed reactor is evacuated until the vacuum degree reaches an absolute pressure of 0.015 MPa.

[0112] (3) The reactor with qualified vacuum degree is heated and stirred at a temperature of 400° C., a rotation speed of 200 r / min, and a holding time of 3 h. During the holding period, the vacuum degree is maintained at an absolute pressure of 0.03 MPa. After heating is completed and cooling is performed, the material is released to obtain the first material.

[0113] (4) The first material is subjected to low-temperature carbonization treatment at a temperature of 700° C. for 4 hours in a nitrogen atmosphere. After the heating is completed and the material is cooled to room temperature, a second material is obtained. The second material has a volatile matter content of 1.3% and a graphitization degree of 90.5%.

[0114] (5) The second material is subjected to oxidation ablation treatment at a temperature of 800°C, a time of 7 hours, and an air flow rate of 3m 3 / h, after heating, cooling to room temperature, the third material was obtained. The average thickness of amorphous carbon in the third material was 160nm, the average ID / IG (peak intensity ratio) of 400 points scanned by Raman spectrometer was 0.34, and the compacted density of the powder under 2 tons was 1.63g / cm 3 , D002 measured by XRD is 0.33604nm.

[0115] (6) The third material is subjected to high-temperature carbonization treatment at a temperature of 1650° C. for 9 hours in a nitrogen atmosphere, and then cooled to room temperature to obtain a natural graphite negative electrode material.

[0116] The argon ion polishing scanning electron microscope image (magnification is 3000 times) of the negative electrode material in this embodiment is as follows Figure 1 shown.

[0117] The argon ion polishing scanning electron microscope image (magnification is 50000 times) of the negative electrode material in this embodiment is as follows Figure 2 shown.

[0118] The ID / IG distribution diagram of the negative electrode material in this embodiment 2 is as follows Figure 3 shown.

[0119] Example 3

[0120] A method for preparing a negative electrode material comprises the following steps:

[0121] (1) 1 kg of a mixture of coal tar and petroleum tar (coking value 75%) and 9 kg of natural graphite (D50 = 25 μm, carbon content 99.96%, pore volume 0.02 cm 3 / g) are added into a mixing device and stirred at high speed to mix the materials evenly to obtain a mixed material.

[0122] (2) The mixed material is placed in a reactor, and the sealed reactor is evacuated until the vacuum degree reaches an absolute pressure of 0.01 MPa.

[0123] (3) The reactor with qualified vacuum degree is heated and stirred at a temperature of 500° C., a rotation speed of 100 rpm, and a holding time of 1 h. During the holding period, the vacuum degree is maintained at an absolute pressure of 0.04 MPa. After heating is completed and cooling is performed, the material is released to obtain the first material.

[0124] (4) The first material is subjected to low-temperature carbonization treatment at a temperature of 800° C. and a high-temperature carbonization time of 1 h in a nitrogen atmosphere. After the heating is completed and the material is cooled to room temperature, a second material is obtained. The second material has a volatile matter content of 1% and a graphitization degree of 92%.

[0125] (5) The second material is subjected to oxidation ablation treatment at a temperature of 900°C, a time of 3 hours, and an air flow rate of 1 m 3 / h, after heating and cooling to room temperature, the third material is obtained. The amorphous carbon thickness of the third material is 100nm, the average ID / IG (peak intensity ratio) of 400 points scanned by Raman spectrometer is 0.19, and the compacted density of the powder under 2 tons is 1.68g / cm 3 , D002 measured by XRD is 0.335932nm.

[0126] (6) The third material is subjected to high-temperature carbonization treatment at a temperature of 1800° C. for 12 h in a nitrogen atmosphere, and then cooled to room temperature to obtain a natural graphite negative electrode material.

[0127] Example 4

[0128] A method for preparing a negative electrode material, which is different from Example 2 in that:

[0129] Step (5): The second material is subjected to oxidation ablation treatment at a temperature of 750°C, a time of 7.5 hours, and an air flow rate of 1 m 3 / h, after heating, cooling to room temperature, the third material was obtained. The amorphous carbon thickness of the third material was 180nm, the average ID / IG (peak intensity ratio) of 400 points scanned by Raman spectrometer was 0.38, and the compacted density of the powder under 2 tons was 1.61g / cm 3 , D002 measured by XRD is 0.336190nm.

[0130] Example 5

[0131] A method for preparing a negative electrode material, which is different from Example 2 in that:

[0132] Step (5): The second material is subjected to oxidation ablation treatment at a temperature of 650°C, a time of 8.5 hours, and an air flow rate of 1 m 3 / h, after heating, cooling to room temperature, the third material was obtained. The amorphous carbon thickness of the third material was 190nm, the average ID / IG (peak intensity ratio) of 400 points scanned by Raman spectrometer was 0.43, and the compacted density of the powder under 2 tons was 1.58g / cm 3 , D002 measured by XRD is 0.336263nm.

[0133] Example 6

[0134] A method for preparing a negative electrode material is substantially the same as that in Example 2, except that in this comparative example, the pore volume of natural graphite is 0.013 cm 3 / g.

[0135] Example 7

[0136] A method for preparing a negative electrode material is substantially the same as that in Example 2, except that in this comparative example, the pore volume of natural graphite is 0.068 cm 3 / g.

[0137] Comparative Example 1

[0138] A method for preparing a negative electrode material comprises the following steps:

[0139] (1) 1.5 kg coal tar pitch (coking value 75%) and 8.5 kg natural graphite (D50 = 15 μm, carbon content 99.95%, pore volume 0.034 cm 3 / g) are added into a mixing device and stirred at high speed to mix the materials evenly to obtain a mixed material.

[0140] (2) The mixed material is placed in a reactor, and the reactor is heated and stirred at a temperature of 400° C., a rotation speed of 200 r / min, and a heat preservation time of 3 h. After heating is completed and cooling is performed, the material is released to obtain a first material.

[0141] (3) The first material is subjected to high-temperature carbonization treatment at a temperature of 1650° C. for 9 hours in a nitrogen atmosphere, and then cooled to room temperature to obtain a natural graphite negative electrode material.

[0142] The scanning electron microscope image of the negative electrode material in this comparative example is as follows Figure 4 shown.

[0143] The ID / IG distribution diagram of the negative electrode material in this comparative example is as follows Figure 5 shown.

[0144] Comparative Example 2

[0145] A method for preparing a negative electrode material comprises the following steps:

[0146] (1) 1.5 kg coal tar pitch (coking value 75%) and 8.5 kg natural graphite (D50 = 15 μm, carbon content 99.95%, pore volume 0.034 cm 3 / g) are added into a mixing device and stirred at high speed to mix the materials evenly to obtain a mixed material.

[0147] (2) The mixed material is placed in a reactor, and the sealed reactor is evacuated until the vacuum degree reaches an absolute pressure of 0.015 MPa.

[0148] (3) The reactor with qualified vacuum degree is heated and stirred at a temperature of 400° C., a rotation speed of 200 r / min, and a holding time of 3 h. During the holding period, the vacuum degree is maintained at an absolute pressure of 0.03 MPa. After heating is completed and cooling is performed, the material is released to obtain the first material.

[0149] (4) The first material is subjected to low-temperature carbonization treatment at a temperature of 700° C. for 4 hours in a nitrogen atmosphere, and cooled to room temperature to obtain a second material. The second material has a volatile matter content of 1.3% and a graphitization degree of 90.5%.

[0150] (5) The second material is subjected to high-temperature carbonization treatment at a temperature of 1650° C. for 6 hours in a nitrogen atmosphere, and then cooled to room temperature to obtain a natural graphite negative electrode material.

[0151] Comparative Example 3

[0152] A method for preparing a negative electrode material, which is different from Example 2 in that:

[0153] Step (5): The second material is subjected to oxidation ablation treatment at a temperature of 950°C, a time of 3 hours, and an air flow rate of 1 m 3 / h, after heating, cooling to room temperature, the third material was obtained. The amorphous carbon thickness of the third material was 80nm, the average ID / IG (peak intensity ratio) of 400 points scanned by Raman spectrometer was 0.15, and the compacted density of the powder under 2 tons was 1.66g / cm 3 , D002 measured by XRD is 0.335914.

[0154] Experimental example

[0155] 1. Performance test of negative electrode materials

[0156] The negative electrode materials obtained in each embodiment and comparative example were subjected to performance tests respectively, and the test methods are as follows:

[0157] 1. Particle size test

[0158] The particle size is measured using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK.

[0159] 2. Compaction density test

[0160] The pressurization method is adopted, which is basically based on the powder compaction density test method described in GBT 24533-2009 Graphite-based negative electrode materials for lithium-ion batteries, with the only difference being that the test pressure in the present invention is 2 tons.

[0161] 3. Scanning electron microscope test

[0162] Scanning electron microscopy (SEM) characterization was performed on a transmission electron microscope with an operating voltage of 200 kV to observe the structure of the negative electrode materials.

[0163] 4. Test of carbon coating thickness

[0164] The material is sectioned using a FIB-SEM device, and any area of ​​the sample section is photographed using a scanning electron microscope at 20,000 times. The center of each particle in the 20,000-fold image is selected, and vertical cross lines are randomly made at the center of the circle. The thickness of the amorphous carbon layer at the intersection of the cross lines and the edge of the particle section is recorded, and the average thickness of the amorphous carbon layer of a single particle is calculated. The average thickness of the amorphous carbon layer of all particles in the 20,000-fold image is then averaged to obtain the average thickness of the carbon coating layer of the sample.

[0165] 5. Raman ID / IG test

[0166] The peak intensity of the material D (1350cm -1 Nearby, belonging to the boundary vibration mode of the disorder-induced hexagonal Brillouin zone, used for defect characterization. ) and G peak intensity (1580cm -1Nearby, belonging to the stretching vibration mode of the carbon atom plane bond, which is related to the degree of graphitization), where the peak intensity ratio of the D peak and the G peak is ID / IG. Using 532nm semiconductor laser, power ≥50mW; test conditions: using neon lamp as signal source, ≥1800 lines of high-resolution grating, test 17086ABScm -1 The luminous line has a full width at half maximum of less than or equal to 1 wave number (FWHM≤1cm -1 ); spatial resolution: ≤0.3μm (XY); ≤1μm (Z); scanning step length is 5μm, surface scanning range: -47μm≤X≤48μm; -47μm≤Y≤48μm, surface scanning 400 points.

[0167] 6. Pore volume test

[0168] The pore volume of the material was measured using a static BET adsorption method using a specific surface area and pore size analyzer.

[0169] 7. True density test

[0170] After the sample was immersed in liquid and exhausted in vacuum, its density at 30°C was tested by the pycnometer method.

[0171] 8. Test of graphitization degree

[0172] When X-rays are projected into a crystal, they are scattered by atoms and electrons in the crystal. Due to the periodic arrangement of atoms in the crystal, there is a fixed phase difference between these scattered waves, which interfere in space, resulting in the mutual reinforcement of scattered waves in certain scattering directions and the mutual cancellation in certain directions, thus causing diffraction. The diffractometer automatically records the diffraction pattern of the sample and analyzes the diffraction pattern to obtain sample information; silicon is used as an internal standard, added to graphite and mixed, and then XRD is tested to calculate d002, and the degree of graphitization = 100×(3.44-d002) / (3.44-3.354) (unit: %).

[0173] The performance test results of the negative electrode materials are shown in Table 1.

[0174] Table 1 Performance test results of negative electrode materials

[0175]

[0176]

[0177] 2. Battery performance test

[0178] The negative electrode materials obtained in each embodiment and comparative example are respectively mixed with CMC, SP and SBR in a pure water solution at a mass ratio of 95:2:1:2 to prepare slurry, and the slurry is coated on the surface of copper foil to prepare a negative electrode sheet; lithium foil is used as a positive electrode sheet, the separator is a microporous polypropylene membrane, and the electrolyte composition is: 1M LiPF6 is dissolved in a mixed solution of EC, DMC and EMC, the volume ratio of EC, DMC and EMC is 1:1:1, and the mixed solution also contains VC with a mass content of 1%. The negative electrode sheet, the positive electrode sheet, the separator and the electrolyte are assembled into a lithium ion battery, and the charge and discharge cut-off voltage is 0.005~2V.

[0179] The performance test of the battery includes: 1) the first reversible capacity; 2) the first coulombic efficiency; 3) 50 cycles at 25°C and 1C, and the expansion rate of the graphite electrode is tested after disassembly; 4) half-cell, lithium sheet as negative electrode, graphite as positive electrode, 3C discharge, and DV / DQ second-order derivative curve. The inflection point of the slope of the curve is the lithium deposition S0C position; the 3C lithium deposition performance of the negative electrode material is approximately positively correlated with the rate performance. The better the 3C lithium deposition performance, the better the rate performance will usually be; 5) capacity retention rate after 300 cycles at 45°C and 1C.

[0180] The specific test results are shown in Table 2.

[0181] Table 2 Battery performance test results

[0182]

[0183]

[0184] Depend on Figure 1 , Figure 4 It can be seen that the method for preparing the negative electrode material of the present invention can effectively fill the organic carbon source into the particles by heating and stirring under negative pressure.

[0185] It can be seen from the performance data of the negative electrode material in Table 1 and the performance data of the battery in Table 2 that, compared with Comparative Example 1, after the organic carbon source fills the interior of the particles in Examples 1-7 and Comparative Examples 2-3, it becomes easier for lithium ions to diffuse inside the material, resulting in a significant reduction in the expansion rate of the electrode of the material and a significant improvement in the 3C lithium plating performance of the material (rate performance).

[0186] According to the performance of negative electrode materials in Table 1 and the performance data of batteries in Table 2, Figure 2 , Figure 3 and Figure 5It can be seen that compared with Comparative Examples 1-2, after oxidative ablation treatment, the amorphous carbon layer on the particle surface of Examples 1-7 and Comparative Example 3 becomes thinner, and the compaction density and the first reversible capacity of the material are significantly improved. The average ID / IG value of the amorphous carbon layer on the particle surface is significantly reduced, and the number of points with a single point value of ID / IG <0.2 is significantly increased, indicating that oxidative ablation can reduce the number of defect sites in the amorphous carbon of the surface coating layer, improve the compatibility of the material surface with the electrolyte, and improve the high-temperature cycle performance, ultimately resulting in a significant improvement in the first Coulomb efficiency of the material and the capacity retention rate during the 45°C cycle.

[0187] Compared with Example 2, the graphite skeleton pore volume of Example 6 is smaller (less than 0.02 cm 3 / g), the content of amorphous carbon filled is low, which is not conducive to the rapid diffusion of lithium ions inside the graphite particles, resulting in the deterioration of the 3C lithium precipitation performance of the material; the graphite skeleton pore volume of Example 7 is large (greater than 0.05cm 3 / g), the content of filled amorphous carbon is relatively high, which leads to a small compaction density of the powder material, which is not conducive to the energy density of the material.

[0188] Compared with Example 2, although Comparative Example 3 also uses heating and stirring under negative pressure to fill the organic matter into the particles, and uses oxidation ablation to improve the number of defect sites in the amorphous carbon layer on the surface of the particles, the oxidation ablation temperature is too high, resulting in the thickness of the surface amorphous carbon layer being too thin, and the active sites of the amorphous carbon layer are basically completely ablated, exposing the worse defect sites of the graphite body, thereby deteriorating the material's 3C lithium precipitation performance and 45°C high-temperature cycle performance.

[0189] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A negative electrode material, characterized in that: The composite particles include a core and an amorphous carbon coating layer located on the surface of the core, wherein the core includes a graphite skeleton and amorphous carbon filled in the graphite skeleton; The thickness of the amorphous carbon coating layer is 10 to 50 nm; The negative electrode material is subjected to Raman spectrum scanning, the number of Raman spectrum scanning points is 400, the average ID / IG value of the Raman spectrum of the negative electrode material is 0.10-0.20, and the number of scanning points with single point values ​​of ID / IG less than 0.2 accounts for more than 60%; The compaction density of the negative electrode material under a pressure of 2 tons is greater than 1.65 g / cm 3 .

2. The negative electrode material according to claim 1, characterized in that Contains at least one of the following features (1) to (2): (1) The thickness of the amorphous carbon coating layer is 10 to 30 nm; (2) The average ID / IG value of the Raman spectrum of the negative electrode material is 0.10-0.14, wherein the number of scanning points with a single point value of ID / IG less than 0.2 accounts for 65%-91%.

3. The negative electrode material according to claim 1, characterized in that Contains at least one of the following features (1) to (8): (1) The particle size Dv50 of the graphite skeleton is 5 to 25 μm; (2) The graphite skeleton comprises natural graphite; (3) The pore volume of the graphite skeleton is 0.02 to 0.05 cm 3 / g; (4) The interlayer spacing d002 of the X-ray diffraction spectrum of the negative electrode material is 0.335775 to 0.335934 nm; (5) The true density of the negative electrode material is greater than 2.190 g / cm 3 ; (6) The pore volume of the negative electrode material is less than 0.005 cm 3 / g; (7) The gram capacity of the negative electrode material is greater than 360 mAh / g; (8) The initial coulombic efficiency of the negative electrode material is greater than 94%.

4. A method for preparing a negative electrode material, characterized in that: The following steps are involved: Heat-treating a mixed system of graphite skeleton and organic carbon source under negative pressure to obtain a first material; The first material is subjected to low-temperature carbonization treatment, oxidation ablation treatment and high-temperature carbonization treatment in sequence.

5. The method for preparing the negative electrode material according to claim 4, characterized in that: The method comprises at least one of the following features (1) to (11): (1) The graphite skeleton comprises natural graphite; (2) The particle size Dv50 of the graphite skeleton is 5 to 25 μm, and the carbon content of the graphite skeleton is greater than 99.9%; (3) The pore volume of the graphite skeleton is 0.02 to 0.05 cm 3 / g; (4) The organic carbon source includes at least one of petroleum asphalt, coal tar pitch and thermoplastic resin; (5) The coking value of the organic carbon source after heating at 550° C. in a protective atmosphere for 2 hours is greater than 70%; (6) The mass ratio of the graphite skeleton to the organic carbon source is 75:25 to 90:10; (7) The vacuum degree during the heat treatment process is less than 0.05 MPa absolute pressure; (8) The vacuum degree of the environment in which the mixed system is located before heat treatment is less than 0.03 MPa in absolute pressure; (9) The temperature of the heat treatment is 300 to 500° C., and the time of the heat treatment is 1 to 5 hours; (10) During the heat treatment, the mixed system is stirred at a speed of 100 to 300 r / min; (11) Also includes: cooling the heat-treated material to room temperature.

6. The method for preparing the negative electrode material according to claim 4, characterized in that: Contains at least one of the following features (1) to (3): (1) The second material obtained by the low-temperature carbonization treatment has a volatile matter content of less than 2% and a graphitization degree of 89% to 92%; (2) The temperature of the low-temperature carbonization treatment is 500 to 800° C., and the time of the low-temperature carbonization treatment is 2 to 8 hours; (3) The low-temperature carbonization treatment is carried out under protective gas conditions.

7. The method for preparing the negative electrode material according to claim 4, characterized in that: Contains at least one of the following features (1) to (3): (1) The third material obtained by the oxidation ablation treatment comprises a graphite core and an amorphous carbon layer; the average thickness of the amorphous carbon layer is 100 to 300 nm; the average value of ID / IG of the Raman spectrum of the third material is 0.19 to 0.50; the powder compaction density of the third material under a pressure of 2 tons is greater than 1.55 g / cm 3 ; The interlayer spacing d002 of the X-ray diffraction pattern of the third material is 0.335932 to 0.336270 nm; (2) The temperature of the oxidation ablation treatment is 600 to 900° C., and the time of the oxidation ablation treatment is 3 to 10 hours; (3) The atmosphere of the oxidation ablation treatment is an oxygen-containing atmosphere with a flow rate of 1 to 5 m 3 / h.

8. The method for preparing the negative electrode material according to claim 4, characterized in that: Contains at least one of the following features (1) to (2): (1) The temperature of the high temperature carbonization treatment is 1500-1800° C., and the time of the high temperature carbonization treatment is 6-12 hours; (2) The high temperature carbonization treatment is carried out under protective gas conditions.

9. A negative electrode sheet, characterized in that: The invention comprises the negative electrode material according to any one of claims 1 to 3, or the negative electrode material prepared by the method for preparing the negative electrode material according to any one of claims 4 to 8.

10. A battery, characterized in that: Includes the negative electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Modified natural graphite material and preparation method thereof, negative pole piece and lithium ion battery

    CN114843508A

  • Low-temperature long-service-life natural graphite negative electrode material as well as preparation method and application thereof

    CN114873591A

  • Modified natural graphite negative electrode material and preparation method thereof

    CN116730333A

Cited By

  • Pole piece and application thereof

    CN120565679A